(untitled) (Research, Society and Development, 2022)
The scarcity of water resources has driven the establishment of priority ways to use good quality resources and the adoption of alternative sources of water, such as that from reuse. The agricultural sector is the one that consumes the most water, about 70% of the water used in the country, with emphasis on the use for the satiety of its large herd and for the irrigation of crops. Irrigation played a fundamental role in the country’s agricultural development and in ensuring food security, enabling production in places with inadequate soil and climatic characteristics. Irrigation with wastewater has proved to be an extremely viable alternative both from an environmental and nutritional point of view for the plant. This study aims to know the scientific production related to the use of wastewater in agriculture, its evolution, areas of concentration and possible gaps. The sample consists of 3555 scientific articles, developed between 1970 and 2021. This sample was analyzed quantitatively, with the support of bibliometric networks. The study shows that the number of publications on the researched topic has increased in recent years, that the main area of concentration of studies is the Environmental area followed by the area of Agrarian and Biological, it also showed that the United States stands out in the development of studies on the subject, followed by China. Brazil assumes an incipient position on the subject. The study made it possible to identify collaborative networks in the development of scientific production, as well as temporal gaps for the production of new studies and discussions on the use of wastewater in agriculture.